Sodium-based solid-state electrolyte, method for producing sodium-based solid-state electrolyte, modified positive electrode active material, modified negative electrode active material, solid-state secondary battery, electrode sheet for solid-state secondary battery, solid-state electrolyte sheet, and electrode for solid-state secondary battery

Through the use of sodium tetraramidicine, water and sodium salts in the secondary battery of solid sodium ion ions, the solid electrolytes of sodium, water and sodium salt are used, and mechanical grinding treatment and element mixing are performed to solve the problem of insufficient solid electrolyte ion conduction and realization. Has high -efficiency charging and discharge performance and stability.

CN119343798APending Publication Date: 2025-01-21INSTITUTE OF SCIENCE TOKYO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380043066.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-26
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the existing solid-state sodium ion secondary batteries, there is room for further improvement in the ion conductivity of the solid electrolyte, which affects the charging and discharging characteristics of the battery.

Method used

A sodium -based solid electrolyte containing sodium, water and sodium salt containing amylocycular state, and the mix of mechanical grinding treatment and specific elements to optimize the composition and structure of electrolytes to improve ionic conduction.

Benefits of technology

The high ionic conductivity of the sodium-based solid electrolyte is achieved, and the charge and discharge performance and stability of the solid-state secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343798A_ABST
    Figure CN119343798A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a sodium-based solid electrolyte having excellent ion conductivity, a method for producing the sodium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, a solid-state secondary battery, an electrode sheet for a solid-state secondary battery, a solid-state electrolyte sheet, and an electrode for a solid-state secondary battery. This sodium-based solid electrolyte contains amorphous sodium tetraborate, water, and a sodium salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sodium-based solid electrolyte, a method for producing a sodium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, a solid-state secondary battery, an electrode sheet for a solid-state secondary battery, a solid electrolyte sheet, and an electrode for a solid-state secondary battery. Background Art

[0002] In the past, liquid electrolytes with high ion conductivity have been used in lithium-ion secondary batteries. However, since liquid electrolytes are flammable, there are safety issues. In addition, since they are in a liquid state, it is difficult to make them compact, and when the battery becomes larger, the capacity limitation also becomes a problem.

[0003] In order to solve the above problems, solid-state lithium-ion secondary batteries using solid electrolytes are being developed as one of the next-generation batteries. In order to obtain the desired charge and discharge characteristics in solid-state lithium-ion secondary batteries, a solid electrolyte having good ion conductivity is required.

[0004] On the other hand, lithium used in lithium ion secondary batteries has problems such as soaring raw material prices and depletion of resources. Therefore, sodium ions have attracted attention as a substitute for lithium ions, and the development of solid-state sodium ion secondary batteries is underway.

[0005] For example, Patent Document 1 discloses a solid sodium ion secondary battery comprising: a solid electrolyte layer composed of a sodium ion conductive oxide; a positive electrode layer; a negative electrode layer; and a collector layer, which is arranged on the main surface of at least one of the positive electrode layer and the negative electrode layer and is composed of a specified metal material.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2018 / 225494 Summary of the invention

[0009] Technical issues to be solved by the invention

[0010] With reference to Patent Document 1, a solid electrolyte used in a secondary battery such as a solid sodium ion secondary battery was studied, and as a result, it was found that there is room for further improvement in the ion conductivity of the solid electrolyte.

[0011] An object of the present invention is to provide a sodium-based solid electrolyte having excellent ion conductivity.

[0012] Furthermore, the present invention also aims to provide a method for producing a sodium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, a solid-state secondary battery, an electrode sheet for a solid-state secondary battery, a solid electrolyte sheet, and an electrode for a solid-state secondary battery.

[0013] Means for solving technical problems

[0014] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention having the following structure.

[0015] (1) A sodium-based solid electrolyte comprising amorphous sodium tetraborate, water, and a sodium salt.

[0016] (2) The sodium-based solid electrolyte according to (1), wherein

[0017] The molar ratio of sodium salt to sodium tetraborate is 0.001 to 1.5.

[0018] The molar ratio of water to sodium tetraborate is 1 to 15. (3) The sodium-based solid electrolyte according to (1) or (2), wherein

[0019] The sodium salt is a compound represented by the formula (1) described later.

[0020] (4) A sodium-based solid electrolyte, wherein:

[0021] Sodium-based solid electrolytes contain Na, B and O.

[0022] The sodium-based solid electrolyte further comprises one or more specific elements selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc and Y,

[0023] When the molar amount of Na, O, and the specific element is expressed by assuming that the molar amount of B in the sodium-based solid electrolyte is 4.0,

[0024] The molar amount of Na is 1.6 to 3.5,

[0025] The molar amount of O is 6.2 to 25.0,

[0026] The molar amount of each of the specific elements is 0.01 to 10.0.

[0027] (5) A method for producing a sodium-based solid electrolyte, which is the method for producing a sodium-based solid electrolyte according to any one of (1) to (4), comprising:

[0028] Step 1, mechanically grinding the sodium oxide containing Na and B;

[0029] Step 2, mixing the product obtained in step 1 and water; and

[0030] Step 3, removing water from the dispersion obtained in step 2 to obtain a sodium-based solid electrolyte,

[0031] Satisfy any one of the requirements 1 to 3 described below.

[0032] (6) The method for producing a sodium-based solid electrolyte according to (5), which satisfies requirement 1,

[0033] Prior to step 1, step 0 is further included: mechanically polishing the sodium oxide containing Na and B in an environment without a specific element source described later.

[0034] (7) A modified positive electrode active material, comprising a positive electrode active material and a coating layer disposed on the positive electrode active material, wherein:

[0035] The coating layer contains the sodium-based solid electrolyte described in any one of (1) to (4).

[0036] (8) A modified negative electrode active material comprising a negative electrode active material and a coating layer disposed on the negative electrode active material, wherein:

[0037] The coating layer contains the sodium-based solid electrolyte described in any one of (1) to (4).

[0038] (9) A solid-state secondary battery comprising, in order, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein:

[0039] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer includes the sodium-based solid electrolyte described in any one of (1) to (4).

[0040] (10) An electrode sheet for a solid-state secondary battery, comprising the sodium-based solid electrolyte according to any one of (1) to (4).

[0041] (11) A solid electrolyte sheet comprising the sodium-based solid electrolyte described in any one of (1) to (4).

[0042] (12) An electrode for a solid-state secondary battery, comprising:

[0043] An active material layer comprises an active material and the sodium-based solid electrolyte described in any one of (1) to (4); and a current collector.

[0044] Effects of the Invention

[0045] According to the present invention, a sodium-based solid electrolyte having excellent ion conductivity can be provided.

[0046] Furthermore, according to the present invention, a method for producing a sodium-based solid electrolyte, a modified positive electrode active material, a modified negative electrode active material, a solid-state secondary battery, an electrode sheet for a solid-state secondary battery, a solid electrolyte sheet, and an electrode for a solid-state secondary battery can also be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a cross-sectional view schematically showing a solid-state sodium ion secondary battery according to a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0048] Hereinafter, the present invention will be described in detail.

[0049] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0050] As a characteristic point of the first embodiment of the sodium-based solid electrolyte of the present invention, it can be cited that it contains various elements in a specified amount. In particular, the following point can be cited: the content of O (oxygen element) is relatively large, and it contains two or more specific elements in a specified amount. In addition, it is believed that O exists as water or OH groups in addition to BO3 or BO4 in the sodium-based solid electrolyte, and it is speculated that a hydration layer with good ion conductivity is formed on the surface side of the sodium-based solid electrolyte due to the high content of O. In addition, the adhesion of this sodium-based solid electrolyte is also excellent, and it is speculated that this point also contributes to the improvement of ion conductivity.

[0051] Furthermore, as a characteristic point of the second embodiment of the sodium-based solid electrolyte of the present invention, the use of amorphous sodium tetraborate and a predetermined component (water, sodium salt) in combination can be cited. If amorphous sodium tetraborate and a predetermined component are used in combination, a soft hydration layer is easily formed on the surface of the sodium tetraborate, and a large amount of sodium derived from the sodium salt is contained in the hydration layer, and as a result, it is presumed that the ion conductivity becomes good.

[0052] Hereinafter, each embodiment of the sodium-based solid electrolyte of the present invention will be described in detail.

[0053] <<First embodiment>>

[0054] The first embodiment of the sodium-based solid electrolyte of the present invention contains Na (sodium element), B (boron element), and O (oxygen element).

[0055] In addition, the first embodiment of the sodium-based solid electrolyte of the present invention also includes one or more specific elements selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si (silicon element), C (carbon element), Sc (scandium element) and Y (yttrium element).

[0056] Furthermore, from the viewpoint of better ion conductivity (hereinafter also referred to as “the viewpoint of better effect of the present invention”), the first embodiment of the sodium-based solid electrolyte of the present invention preferably contains one or more specific elements selected from the group consisting of F (fluorine), Cl (chlorine), Br (bromine), I (iodine), S (sulfur), P (phosphorus), Si (silicon), Se (selenium), Te (tellurium), C (carbon), Sb (antimony), As (arsenic), Sc (scandium), Y (yttrium), Zr (zirconium), Ti (titanium), Hf (hafnium) and N (nitrogen).

[0057] Examples of the periodic table Group 4 elements include Ti, Zr, Hr, and Rf.

[0058] Examples of the periodic table Group 15 elements include N, P, As, Sb, Bi, and Mc.

[0059] Examples of the periodic table Group 16 elements include S, Se, Te, Po, and Lv.

[0060] Examples of the periodic table Group 17 elements include F, Cl, Br, I, At, and Ts.

[0061] The types of specific elements contained in the first embodiment of the sodium-based solid electrolyte of the present invention may be 2 or more. Among them, from the viewpoint of the better effect of the present invention, the types of specific elements contained in the sodium-based solid electrolyte are preferably 2 or more, more preferably 2 to 5, and further preferably 2 to 4.

[0062] The first embodiment of the sodium-based solid electrolyte of the present invention preferably contains two or more specific elements selected from the group consisting of F, S, N, P and C, more preferably contains two or more specific elements selected from the group consisting of F, S, C and N, and further preferably contains three specific elements of F, S and N.

[0063] As described later, when manufacturing the first embodiment of the sodium-based solid electrolyte of the present invention, sodium tetraborate is preferably used as a raw material. At this time, the sodium tetraborate used is usually a compound represented by Na2B4O7, which is mainly composed of Na, B and O, but in the present invention, it is also possible to deviate from the above standard value. More specifically, as sodium tetraborate, it is preferably composed of Na 2+ x B 4+y O 7+z(-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3). That is, when the molar amount of Na is expressed by setting the molar amount of B to 4.0, the molar amount of Na is preferably 1.6 to 2.5, and the molar amount of O is preferably 6.2 to 7.9. In other words, when the molar content of B is set to 4.0, the relative value of the molar content of Na is preferably 1.6 to 2.5, and the molar amount of O is preferably 6.2 to 7.9.

[0064] In the first embodiment of the sodium-based solid electrolyte of the present invention, when the molar amount of B in the sodium-based solid electrolyte is set to 4.0 to represent the molar amount of Na, the molar amount of Na is 1.6 to 3.5. That is, when the molar content of B is set to 4.0, the relative value of the molar content of Na is 1.6 to 3.5.

[0065] Among them, from the viewpoint of more excellent effects of the present invention, when the molar amount of Na is expressed as 4.0, the molar amount of Na is preferably 1.6 to 3.2, more preferably 1.9 to 3.2, and further preferably 2.0 to 3.2.

[0066] In the first embodiment of the sodium-based solid electrolyte of the present invention, when the molar amount of B in the sodium-based solid electrolyte is set to 4.0 to represent the molar amount of O, the molar amount of O is 6.2 to 25.0. That is, when the molar content of B is set to 4.0, the relative value of the molar content of O is 6.2 to 25.0.

[0067] Among them, from the viewpoint of more excellent effects of the present invention, when the molar amount of O is represented by assuming that the molar amount of B in the sodium-based solid electrolyte is 4.0, the molar amount of O is preferably 8.0 to 23.0, and more preferably 10.0 to 23.0.

[0068] In the first embodiment of the sodium-based solid electrolyte of the present invention, when the molar amount of B in the sodium-based solid electrolyte is set to 4.0 to represent the molar amount of the specific element, the molar amount of each specific element is 0.01 to 10.0. That is, when the molar content of B is set to 4.0, the relative value of the molar content of each specific element is 0.01 to 10.0.

[0069] Among them, from the viewpoint of more excellent effects of the present invention, when the molar amount of the specific element is represented by the molar amount of B in the sodium-based solid electrolyte being 4.0, the molar amount of each specific element is preferably 0.01 to 6.0, more preferably 0.1 to 5.0, and further preferably 0.1 to 3.0.

[0070] As described above, in the first embodiment of the sodium-based solid electrolyte of the present invention, two or more specific elements are included. Thus, for example, in the case where the first embodiment of the sodium-based solid electrolyte of the present invention includes two specific elements, a specific element A and an element of a different type from the specific element A, namely a specific element B, when the molar amount of B in the sodium-based solid electrolyte is set to 4.0, the molar amount of the specific element A and the molar amount of the specific element B are 0.01 to 10.0, respectively. And, for example, in the case where the first embodiment of the sodium-based solid electrolyte of the present invention includes three specific elements, namely a specific element A, an element of a different type from the specific element A, namely a specific element B, and an element of a different type from the specific elements A and B, namely a specific element C, when the molar amount of B in the sodium-based solid electrolyte is set to 4.0, the molar amount of the specific element A, the molar amount of the specific element B, and the molar amount of the specific element C are 0.01 to 10.0, respectively.

[0071] The contents of Na, B and specific elements in the first embodiment of the sodium-based solid electrolyte of the present invention are determined by known elemental analysis. As an elemental analysis method, for example, Na and B are analyzed by ICP-OES (Inductivelycoupled plasma optical emission spectrometry), one specific element, namely N, is analyzed by an inert gas fusion method, and one specific element, namely F and S, is analyzed by combustion ion chromatography. Regarding O, the analysis mass of elements other than O can be added and calculated as a difference from the total amount of powder. In addition, the method for calculating the content of each element is not limited to the above. Considering the structure of the compound used, the content of other elements can be estimated based on the analysis results of the content of one element.

[0072] From the contents of the elements calculated by elemental analysis, the molar amounts of Na, O, and the specific element were calculated when the molar amount of B was set to 4.0.

[0073] As one of the preferred modes of the composition of the first embodiment of the sodium-based solid electrolyte of the present invention, there can be cited a sodium-based solid electrolyte comprising Na, B, O, F, S and N, and when the molar amount of B is set to 4.0, the molar amount of Na is 1.6 to 3.5 (preferably 1.6 to 3.0), the molar amount of O is 6.2 to 25.0, the molar amount of F is 0.01 to 10.0, the molar amount of S is 0.01 to 2.0, and the molar amount of N is 0.01 to 1.0.

[0074] The preferred range of the molar ratio of each of the above elements is as described above.

[0075] In addition, the first embodiment of the sodium-based solid electrolyte of the present invention may contain Na, B, O, and other elements other than the specific element.

[0076] The method for manufacturing the first embodiment of the sodium-based solid electrolyte of the present invention will be described in detail in the latter section, but the sodium-based solid electrolyte of the present invention is preferably manufactured by a manufacturing method accompanied by mechanical grinding. For example, by mechanically grinding the raw material of the first embodiment of the sodium-based solid electrolyte of the present invention (for example, a sodium-based oxide containing Na and B), the crystalline component in the raw material can be amorphized, and as a result, it is presumed that it becomes easy to form a hydration layer with excellent ion conductivity.

[0077] In the first embodiment of the sodium-based solid electrolyte of the present invention, from the viewpoint of the better effect of the present invention, a sodium-based solid electrolyte is preferably one in which there is no peak originating from Na2B4O7 crystals in the X-ray diffraction pattern obtained from X-ray diffraction measurement using CuKα rays.

[0078] In the present specification, "there is no peak derived from Na2B4O7 crystals" means that there is no peak derived from sodium tetraborate crystals whose peak top is located in the diffraction angle 2θ range of 5.0° to 70.0° in the X-ray diffraction pattern and the intensity ratio obtained by the following intensity measurement method is greater than 10.0.

[0079] Intensity measurement method: In the X-ray diffraction spectrum of the sodium-based solid electrolyte obtained from the X-ray diffraction measurement using CuKα rays, the average intensity in the range of diffraction angle 2θ of 5.0° to 70.0° is calculated. The ratio of the peak intensity at the peak top of the target peak to the calculated average intensity (peak intensity of the target peak / average intensity) is taken as the intensity ratio.

[0080] In other words, when the above-mentioned intensity ratios of the peaks originating from sodium tetraborate crystals whose peak tops are located in the diffraction angle 2θ in the range of 5.0° to 70.0° in the above-mentioned X-ray diffraction pattern are all less than 10.0, the sodium-based solid electrolyte is set to have no peak originating from Na2B4O7 crystals.

[0081] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.

[0082] Among them, from the viewpoint of the better effect of the present invention, the first embodiment of the sodium-based solid electrolyte of the present invention is preferably derived from the peak of the sodium tetraborate crystals whose peak top is located in the diffraction angle 2θ in the range of 5.0° to 70.0° in the above-mentioned X-ray diffraction spectrum and there is no peak with the above-mentioned intensity ratio of 8.0 or more, more preferably there is no peak with the above-mentioned intensity ratio of 5.0 or more, further preferably there is no peak with the above-mentioned intensity ratio of 3.0 or more, and particularly preferably there is no peak with the above-mentioned intensity ratio of 2.0 or more.

[0083] In addition, examples of sodium tetraborate crystals include α-type crystals of anhydrous form (Na2B4O7), γ-type crystals of anhydrous form (Na2B4O7), and crystals of tetrahydrate (Na2B4O7·4H2O).

[0084] Crystals of pentahydrate (Na2B4O7·5H2O or Na2B4O5(OH)4·3H2O) and crystals of decahydrate (Na2B4O7·10H2O or Na2B4O5(OH)4·8H2O).

[0085] The peak position and crystal plane of the peak derived from the sodium tetraborate crystal measured by X-ray diffraction measurement using CuKα rays are shown below for each crystal. In addition, the "peak position" refers to the diffraction angle 2θ (°) at the peak top of the peak.

[0086] As peaks derived from α-type crystals of anhydrous sodium tetraborate, for example, there can be cited a peak derived from the (011) plane appearing in the range of 13.5 to 13.9°, a peak derived from the (102) plane appearing in the range of 22.5 to 22.9°, and a peak derived from the (202) plane appearing in the range of 33.4 to 33.8°.

[0087] As peaks derived from γ-type crystals of anhydrous sodium tetraborate, for example, there can be cited a peak derived from the (02-2) plane appearing in the range of 20.9 to 21.3°, a peak derived from the (2-1-2) plane appearing in the range of 29.8 to 30.2°, and a peak derived from the (210) plane appearing in the range of 32.2 to 32.6°.

[0088] Examples of peaks derived from the crystals of sodium tetraborate tetrahydrate include a peak derived from the (011) plane having a peak position in the range of 11.0 to 11.4°, a peak derived from the (002) plane having a peak position in the range of 11.8 to 12.2°, and a peak derived from the (200) plane having a peak position in the range of 26.3 to 26.7°.

[0089] As peaks derived from the crystals of sodium tetraborate pentahydrate, for example, there can be cited a peak derived from the (202) plane appearing in the range of 20.1 to 20.5°, a peak derived from the (31-2) plane appearing in the range of 25.7 to 26.1°, and a peak derived from the (303) plane appearing in the range of 30.4 to 30.8°.

[0090] Examples of peaks derived from the crystals of sodium tetraborate decahydrate (also known as borax) include a peak derived from the (021) plane with a peak position in the range of 15.4 to 15.8°, a peak derived from the (022) plane with a peak position in the range of 18.1 to 18.5°, and a peak derived from the (132) plane with a peak position in the range of 31.4 to 31.8°. In addition, a peak derived from the (33-2) plane with a peak position in the range of 34.8 to 35.2° can be cited.

[0091] <<Second embodiment>>

[0092] A second embodiment of the sodium-based solid electrolyte of the present invention includes amorphous sodium tetraborate, water, and a sodium salt.

[0093] Hereinafter, each component will be described in detail.

[0094] (Sodium tetraborate in amorphous state)

[0095] Generally, the sodium tetraborate included in the second embodiment is a compound represented by Na2B4O7, which is mainly composed of Na, B and O. However, in the present invention, the above standard value may be deviated. More specifically, as sodium tetraborate, it is preferred to be composed of Na 2+x B 4+y O 7+z A compound represented by (-0.3<x<0.3, -0.3<y<0.3, -0.3<z<0.3).

[0096] Furthermore, the sodium tetraborate contained in the second embodiment of the sodium-based solid electrolyte of the present invention is in an amorphous state.

[0097] Sodium tetraborate in an amorphous state (hereinafter also referred to as "specific sodium tetraborate") is sodium tetraborate in which, in an X-ray diffraction spectrum obtained from an X-ray diffraction measurement using CuKα rays, there is no peak derived from Na2B4O7 crystals. That is, in the X-ray diffraction spectrum of the specific sodium tetraborate obtained from the X-ray diffraction measurement using CuKα rays, there is no peak derived from sodium tetraborate crystals having a peak top located in the range of a diffraction angle 2θ of 5.0° to 70.0° and a peak having an intensity ratio of 10.0 or more obtained by the intensity measurement method described in the first embodiment.

[0098] The above X-ray diffraction measurement was performed using CuKα rays and under the measurement conditions of 0.01° / step, 3° / minute.

[0099] Among them, from the viewpoint of more excellent effects of the present invention, the specific sodium tetraborate is preferably a peak derived from sodium tetraborate crystals having a peak top located in the range of a diffraction angle 2θ of 5.0° to 70.0° in the above-mentioned X-ray diffraction spectrum, and there is no peak with the above-mentioned intensity ratio of 8.0 or more, more preferably there is no peak with the above-mentioned intensity ratio of 5.0 or more, further preferably there is no peak with the above-mentioned intensity ratio of 3.0 or more, and particularly preferably there is no peak with the above-mentioned intensity ratio of 2.0 or more.

[0100] The specific example of the sodium tetraborate crystal, and the peak position and crystal plane of the peak derived from the sodium tetraborate crystal measured by X-ray diffraction measurement using CuKα rays are as described in the first embodiment.

[0101] The content of the specific sodium tetraborate in the second embodiment of the sodium-based solid electrolyte of the present invention is not particularly limited.

[0102] The method for producing specific sodium tetraborate will be described in detail later, but it is preferably produced by a production method accompanied by mechanical grinding. As the mechanical grinding treatment implemented on sodium tetraborate, the mechanical grinding treatment implemented in step 1A described later can be cited, and the details will be described in detail later.

[0103] By subjecting sodium tetraborate to mechanical milling, sodium tetraborate can be amorphized, and as a result, it is presumed that a hydrated layer having excellent ion conductivity is easily formed.

[0104] (water)

[0105] The second embodiment of the sodium-based solid electrolyte of the present invention contains water.

[0106] The content of water in the second embodiment of the sodium-based solid electrolyte of the present invention is not particularly limited. Among them, from the viewpoint of the better effect of the present invention, the molar ratio of water to specific sodium tetraborate in the second embodiment of the sodium-based solid electrolyte of the present invention (molar amount of water / molar amount of specific sodium tetraborate) is preferably 1 to 15, more preferably 1 to 13, further preferably 1 to 10, particularly preferably 2 to 8, and most preferably 2 to 6.

[0107] (Sodium salt)

[0108] A second embodiment of the sodium-based solid electrolyte of the present invention contains a sodium salt.

[0109] The type of the sodium salt is not particularly limited, and examples thereof include the sodium salts exemplified in the step 1A described later, which will be described in detail later.

[0110] The content of the sodium salt in the second embodiment of the sodium-based solid electrolyte of the present invention is not particularly limited.

[0111] In the second embodiment of the sodium-based solid electrolyte of the present invention, the mass ratio of the content of the above-mentioned sodium salt to the content of the specific sodium tetraborate (the mass of the content of the sodium salt / the mass of the content of the specific sodium tetraborate) is not particularly limited. Among them, from the viewpoint of the better effect of the present invention, the molar ratio of the sodium salt to the specific sodium tetraborate in the second embodiment of the sodium-based solid electrolyte of the present invention (the molar amount of the sodium salt / the molar amount of the specific sodium tetraborate) is preferably 0.001 to 1.5, more preferably 0.001 to 1.2, further preferably 0.01 to 1.2, particularly preferably 0.1 to 1.2, and most preferably 0.5 to 1.2.

[0112] The molar ratio of each component in the second embodiment of the sodium-based solid electrolyte of the present invention can be determined using a known method. For example, the elemental analysis described in the first embodiment can be used.

[0113] <Method for producing sodium-based solid electrolyte>

[0114] The method for producing the sodium-based solid electrolyte of the present invention (first embodiment and second embodiment) is not particularly limited, but from the viewpoint of being able to produce the sodium-based solid electrolyte of the present invention with good productivity, a production method including the following steps 1A to 3A is preferred.

[0115] Step 1A: a step of subjecting a sodium-based oxide containing Na and B to mechanical milling in the presence of a specific element source containing one or more elements selected from a specific element group.

[0116] Step 2A: A step of mixing the product obtained in step 1A and water.

[0117] Step 3A: a step of removing water from the dispersion obtained in step 2A to obtain a sodium-based solid electrolyte.

[0118] Hereinafter, the steps of the above-mentioned manufacturing method will be described in detail.

[0119] (Process 1A)

[0120] Step 1A is a step of subjecting a sodium-based oxide containing Na and B to mechanical milling in the presence of a specific element source.

[0121] Hereinafter, the materials used in this step 1A will be described in detail, and then the steps will be described in detail.

[0122] The specific element source contains one or more elements selected from the group consisting of periodic table Group 4 elements, periodic table Group 15 elements, periodic table Group 16 elements, periodic table Group 17 elements, Si, C, Sc, and Y. Among them, the specific element source preferably contains one or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, and N. The specific element source only needs to contain one or more of the above elements, and may be composed of one compound or two or more compounds. For example, the specific element source can be composed of a compound containing one or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, or can be composed of compound 1 and compound 2, wherein compound 1 contains at least one element selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and compound 2 contains an element selected from the above group that is different from the element selected from the above group contained in compound 1.

[0123] The specific element source preferably contains two or more elements selected from the group consisting of periodic table Group 4 elements, periodic table Group 15 elements, periodic table Group 16 elements, periodic table Group 17 elements, Si, C, Sc and Y, more preferably contains 2 to 5 elements, and further preferably contains 2 to 4 elements.

[0124] The specific element source preferably contains 2 to 4 elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf and N, and more preferably contains 3 elements.

[0125] As the compound contained in the specific element source, a salt is preferred, and a sodium salt (particularly, sodium imide salt) is more preferred.

[0126] As the sodium salt, a compound represented by formula (1) is preferred.

[0127] Formula (1)NaN(R f1 SO2)(R f2 SO2)

[0128] R f1 and R f2 Each independently represents a halogen atom or a perfluoroalkyl group.

[0129] R f1 and R f2 In the case of a perfluoroalkyl group, the number of carbon atoms in the perfluoroalkyl group is not particularly limited.

[0130] R f1 and R f2 It is preferably a halogen atom or a perfluoroalkyl group having 1 to 6 carbon atoms, more preferably a halogen atom or a perfluoroalkyl group having 1 to 2 carbon atoms, and still more preferably a halogen atom. If the volume of the terminal group increases, the steric hindrance increases, which becomes a factor that hinders ion conduction. Therefore, R f1 and R f2 In the case of a perfluoroalkyl group, the one having a smaller number of carbon atoms is preferred.

[0131] The following are examples of compounds contained in the specific element source. In addition, among the compounds exemplified below, as described above, a compound containing only one specific element can be used together with other compounds containing at least one other specific element so that the specific element source contains two or more specific elements.

[0132] (L-1) Inorganic sodium salts: inorganic fluoride salts such as NaPF6, NaBF4, NaAsF6 and NaSbF6; perhalide salts such as NaClO4 and NaIO4; inorganic chloride salts such as NaAlCl4.

[0133] (L-2) Fluorine-containing organic sodium salts: perfluoroalkyl sulfonates such as NaCF3SO3; perfluoroalkyl sulfonimide salts such as NaN(CF3SO2)2, NaN(CF3CF2SO2)2, NaN(FSO2)2 and NaN(CF3SO2)(C4F9SO2); perfluoroalkyl sulfonyl methyl salts such as NaC(CF3SO2)3.

[0134] (L-3) Oxalate borate salts: sodium bis(oxalato)borate and sodium difluorooxalatoborate.

[0135] In addition to the above, NaF, NaCl, NaBr, NaI, Na2SO4, NaNO3, Na2CO3 and CH3COONa can also be mentioned.

[0136] Among them, NaPF6, NaBF4, NaAsF6, NaSbF6, NaClO4, Na(R f1 SO3)、NaN(R f1 SO2)2, NaN(FSO2)2 or NaN(R f1 SO2)(R f2 SO2); more preferably NaPF6, NaBF4, NaN(R f1 SO2)2, NaN(FSO2)2 or NAN(R f1 SO2)(R f2 SO2).

[0137] Here, R f1 and Rf2 Each independently represents a perfluoroalkyl group.

[0138] The usage amount of the specific element source is not particularly limited, and the usage amount can be appropriately adjusted in order to obtain the sodium-based solid electrolyte of the present invention as described above.

[0139] The usage-amount of the specific element source is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, based on 100 parts by mass of the sodium-based oxide containing Na and B.

[0140] Examples of sodium oxides containing Na and B include Na2B4O7, Na2B8O 13 、Na2B6O 10 and Na3B7O 12 wait.

[0141] Mechanical grinding is a process of pulverizing a sample while applying mechanical energy to the sample.

[0142] As mechanical grinding treatment, for example, a ball mill, a vibration mill, a turbine mill and a disc mill can be cited, and from the viewpoint of being able to manufacture the sodium-based solid electrolyte of the present invention with good productivity, a ball mill is preferred. As a ball mill, for example, a vibration ball mill, a rotary ball mill and a planetary ball mill can be cited, and a planetary ball mill is more preferred.

[0143] As the conditions for the ball milling treatment, appropriate conditions can be selected according to the raw materials used.

[0144] There is no particular restriction on the material of the grinding balls (media) used in ball milling. For example, agate, silicon nitride, stabilized zirconia (YSZ), alumina and iron-based alloys can be mentioned. From the perspective of being able to manufacture the sodium-based solid electrolyte of the present invention with good productivity, stabilized zirconia (YSZ) is preferred.

[0145] The average particle size of the grinding balls is not particularly limited, but from the viewpoint of being able to manufacture the sodium-based solid electrolyte of the present invention with good productivity, it is preferably 1 to 10 mm, and more preferably 3 to 7 mm. The above average particle size is a value obtained by measuring the diameters of 50 random grinding balls and arithmetically averaging these. In the case where the grinding balls are not spherical, the major diameter is set as the diameter.

[0146] The number of grinding balls used in ball milling is not particularly limited, but is preferably 10 to 100, more preferably 40 to 60, from the viewpoint of being able to produce the sodium-based solid electrolyte of the present invention with good productivity.

[0147] There is no particular restriction on the material of the grinding pot used in ball milling. For example, agate, silicon nitride, stabilized zirconia (YSZ), alumina and iron-based alloys can be mentioned. From the perspective of being able to manufacture the sodium-based solid electrolyte of the present invention with good productivity, stabilized zirconia (YSZ) is preferred.

[0148] The rotation speed during ball milling is not particularly limited, but is preferably 200 to 700 rpm, more preferably 350 to 550 rpm, from the viewpoint of being able to produce the sodium-based solid electrolyte of the present invention with good productivity.

[0149] The ball milling treatment time is not particularly limited, but is preferably 10 to 200 hours, more preferably 20 to 140 hours, from the viewpoint of being able to produce the sodium-based solid electrolyte of the present invention with good productivity.

[0150] The ball milling may be performed in the air or in an inert gas (eg, argon, helium, or nitrogen) atmosphere.

[0151] (Process 2A)

[0152] Step 2A is a step of mixing the product obtained in step 1A with water. By performing this step, the sodium-based oxide containing Na and B obtained in step 1A and subjected to mechanical milling treatment and water are mixed to generate the sodium-based solid electrolyte of the present invention containing a large amount of O (oxygen element).

[0153] The amount of water used is not particularly limited, but from the viewpoint of achieving more excellent effects of the present invention, the amount of water used is preferably 10 to 200 parts by mass, more preferably 50 to 150 parts by mass, based on 100 parts by mass of the product obtained in step 1A.

[0154] The method for mixing the product obtained in step 1A and water is not particularly limited, and the products may be mixed all at once, or water may be added stepwise to the product obtained in step 1A and mixed.

[0155] During the mixing, ultrasonic treatment may be performed as necessary.

[0156] The time of the ultrasonic treatment is not particularly limited, but is preferably 10 minutes to 5 hours from the viewpoint of achieving more excellent effects of the present invention.

[0157] (Process 3A)

[0158] Step 3A is a step of removing water from the dispersion obtained in step 2A to obtain a sodium-based solid electrolyte.

[0159] In this step, water can be removed from the dispersion in such a way that a sodium-based solid electrolyte is formed and water remains in the sodium-based solid electrolyte. That is, in step 3A, a part of the water in the dispersion is removed to obtain the above-mentioned sodium-based solid electrolyte containing water, thereby obtaining a predetermined sodium-based solid electrolyte.

[0160] The method for removing water from the dispersion obtained in step 2A is not particularly limited, and water can be evaporated by heating or by vacuum drying. By adjusting the amount of water removed within the above range, the water content contained in the sodium-based solid electrolyte can be appropriately adjusted.

[0161] As this process, it is preferred to dry the above dispersion under vacuum conditions to obtain a sodium-based solid electrolyte containing water. Vacuum conditions refer to drying treatment under a specified reduced pressure environment and at a specified temperature. As more specific vacuum conditions, for example, conditions below 20Pa) and below 40°C can be cited. The lower limit of the above pressure is not particularly limited, for example, it is above 10Pa. In addition, the lower limit of the above temperature is not particularly limited, for example, it is above 20°C.

[0162] The treatment time of the vacuum drying treatment may be appropriately selected according to the pressure and temperature, the amount of water contained in the dispersion, the target water content of the sodium-based solid electrolyte, and the like, and is, for example, 120 to 900 minutes.

[0163] In addition, when a sodium-based solid electrolyte is manufactured by a manufacturing method including steps 1A to 3A (including steps 1 to 3 described later and satisfying requirement 1 described later), the following step 0 can be implemented: before the above-mentioned step 1A, the sodium-based oxide containing Na and B is subjected to mechanical grinding treatment in an environment in the absence of a specific element source, and preferably step 0 is implemented.

[0164] A preferred embodiment of the mechanical polishing treatment performed in step 0 is the same as a preferred embodiment of the mechanical polishing treatment performed in step 1A described above.

[0165] (Process 1B~3B)

[0166] As another preferred embodiment of the method for producing the sodium-based solid electrolyte of the present invention, a production method including the following steps 1B to 3B is preferred.

[0167] Step 1B: a step of subjecting the sodium-based oxide containing Na and B to mechanical polishing.

[0168] Step 2B: A step of mixing the product obtained in step 1B, water, and a specific element source.

[0169] Step 3B: a step of removing water from the dispersion obtained in step 2B to obtain a sodium-based solid electrolyte.

[0170] The difference between step 1B and step 1A is that, in step 1A, the mechanical milling process is performed in the presence of a specific element source, whereas in step 1B, the mechanical milling process is performed without using a specific element source.

[0171] A preferred embodiment of the mechanical polishing treatment performed in step 1B is the same as a preferred embodiment of the mechanical polishing treatment performed in step 1A.

[0172] The difference between step 2B and step 2A is that in step 2B, the product obtained in step 1B, water, and a specific element source are mixed.

[0173] The specific element source used in step 2B is the same as the specific element source used in step 1A.

[0174] The amount of the specific element source used in step 2B is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, based on 100 parts by mass of the product obtained in step 1B.

[0175] The procedure of step 2B is not particularly limited, and may be a method of mixing the product obtained in step 1B, water, and a specific element source all at once (method 1), a method of mixing the product obtained in step 1B and water to prepare a dispersion, and then mixing the obtained dispersion with a specific element source (method 2), a method of mixing the product obtained in step 1B and water to prepare a dispersion 1, mixing the specific element source and water to prepare a solution 2, and mixing the dispersion 1 and the solution 2 (method 3), or a method of mixing the product obtained in step 1B after preparing a solution 2 (method 4). When mixing the product obtained in step 1B and water, a dispersion treatment such as ultrasonic treatment may be appropriately performed.

[0176] The steps of process 3B are the same as those of process 3A.

[0177] (Process 1C~3C)

[0178] As another preferred embodiment of the method for producing the sodium-based solid electrolyte of the present invention, a production method including the following steps 1C to 3C is preferred.

[0179] Step 1C: a step of subjecting the sodium-based oxide containing Na and B to mechanical polishing.

[0180] Step 2C: a step of mixing the product obtained in step 1C and water.

[0181] Step 3C: a step of mixing a product obtained by removing water from the dispersion obtained in step 2C and a specific element source to obtain a sodium-based solid electrolyte.

[0182] The steps of step 1C are the same as those of step 1B.

[0183] The steps of process 2C are the same as those of process 2A.

[0184] The difference between step 3C and step 3A is that a product obtained by removing water from the dispersion obtained in step 2C and a specific element source are mixed. In step 3C, the method for removing water from the dispersion obtained in step 2C is the same as that in step 3A, including a preferred embodiment.

[0185] The specific element source used in step 3C is the same as the specific element source used in step 1A.

[0186] The amount of the specific element source used in step 3C is preferably 1 to 300 parts by mass, more preferably 100 to 200 parts by mass, based on 100 parts by mass of the product obtained by removing water from the dispersion obtained in step 2C.

[0187] The method of mixing the product obtained by removing water from the dispersion obtained in step 2C and the specific element source is not particularly limited, and a method in which a solution obtained by dissolving the specific element source in water is impregnated in the product and the two are mixed may be used.

[0188] That is, a preferred embodiment of the method for producing the sodium-based solid electrolyte of the present invention comprises:

[0189] Step 1, mechanically grinding the sodium oxide containing Na and B;

[0190] Step 2, mixing the product obtained in step 1 and water; and

[0191] Step 3, removing water from the dispersion obtained in step 2 to obtain a sodium-based solid electrolyte,

[0192] The production method that satisfies any one of the following requirements 1 to 3 can be mentioned.

[0193] Requirement 1: The mechanical polishing treatment in step 1 is performed in the presence of a specific element source.

[0194] Requirement 2: In step 2, the product, water and a specific element source are mixed.

[0195] Requirement 3: In step 3, a product obtained by removing water from the dispersion obtained in step 2 and a specific element source are mixed to obtain a sodium-based solid electrolyte.

[0196] Preferred embodiments of the treatments performed in each step and the components used are as described above. In addition, as described above, by adjusting the amount of water removed, the content of water contained in the sodium-based solid electrolyte can be appropriately adjusted.

[0197] <Dispersion liquid>

[0198] The dispersion of the present invention comprises the sodium-based solid electrolyte of the present invention and a solvent (eg, an organic solvent, water). The dispersion of the present invention is in a liquid state and can be applied to various objects to be coated, and can be used to produce a solid electrolyte layer.

[0199] In the present specification, the dispersion of the present invention refers to an embodiment in which the content of the solvent in the dispersion is 80% by mass or more.

[0200] The dispersion liquid of the present invention may contain other components in addition to the sodium-based solid electrolyte of the present invention and the solvent.

[0201] As other components, a binder can be mentioned.

[0202] Examples of the binder include various organic high molecular compounds (polymers).

[0203] The organic polymer compound constituting the binder may be in a particulate form or may be in a non-particulate form.

[0204] Examples of the binder include water-soluble binders.

[0205] As the water-soluble binder, there can be mentioned a polymer containing a repeating unit having a structure containing a hydroxyl group and the above-mentioned polymer in which at least a part of the hydroxyl group is substituted with at least one selected from the group consisting of an alkyl group, a hydroxyalkyl group and a carboxyalkyl group. As the above-mentioned water-soluble binder, for example, there can be mentioned carboxymethyl cellulose.

[0206] In addition, as other components, other solid electrolytes other than the sodium-based solid electrolyte of the present invention can be cited. Other solid electrolytes refer to solid electrolytes that can allow ions to move inside. As solid electrolytes, inorganic solid electrolytes are preferred.

[0207] Examples of other solid electrolytes include sulfide-based inorganic solid electrolytes, oxide-based inorganic solid electrolytes, halide-based inorganic solid electrolytes, and hydride-based solid electrolytes.

[0208] The method for producing the dispersion of the present invention is not particularly limited, and examples thereof include a method comprising the above-mentioned steps 1A and 2A and a method comprising steps 1B and 2B.

[0209] <Application>

[0210] The sodium solid electrolyte of the present invention shows excellent ion conductivity, so it can be applied to various purposes. The sodium solid electrolyte of the present invention can be used in various batteries (for example, solid secondary battery, solid oxide fuel cell, solid oxide water vapor electrolysis) for example. Wherein, the sodium solid electrolyte of the present invention is preferably used in solid sodium ion secondary battery.

[0211] More specifically, the sodium-based solid electrolyte of the present invention is preferably used to form a solid electrolyte contained in at least any one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer in a solid-state secondary battery. Among them, the sodium-based solid electrolyte of the present invention is preferably used to form a solid electrolyte contained in the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer in a solid-state sodium ion secondary battery. In addition, the sodium-based solid electrolyte of the present invention is preferably used as a solid electrolyte contained in any one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer in a solid-state sodium ion secondary battery.

[0212] Furthermore, the sodium-based solid electrolyte of the present invention is preferably used as a coating material for coating the surface of a positive electrode active material. That is, as one of the preferred embodiments of the present invention, a modified positive electrode active material can be cited, which has a positive electrode active material and a coating layer disposed on the positive electrode active material, and the coating layer includes the sodium-based solid electrolyte of the present invention.

[0213] In addition, the sodium-based solid electrolyte of the present invention is preferably used as a coating material for coating the surface of the negative electrode active material. That is, as one of the preferred embodiments of the present invention, a modified negative electrode active material can be cited, which has a negative electrode active material and a coating layer disposed on the negative electrode active material, and the coating layer includes the sodium-based solid electrolyte of the present invention.

[0214] When the sodium-based solid electrolyte of the present invention is used, it is preferred that the sodium-based solid electrolyte of the present invention be subjected to a pressure treatment and molded into a predetermined shape for use.

[0215] The method of the pressure treatment is not particularly limited, and examples thereof include a method using a known pressure device.

[0216] The pressure applied during the pressurization treatment is not particularly limited, and the optimal pressure can be appropriately selected. However, from the viewpoint of achieving more excellent effects of the present invention, the pressure is preferably 5 to 1500 MPa, and more preferably 10 to 600 MPa.

[0217] The time of the pressurization treatment is not particularly limited, but is preferably 1 second to 0.5 hour, more preferably 2 seconds to 0.2 hour, from the viewpoint of more excellent effects of the present invention and productivity.

[0218] Furthermore, during the pressurization treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 40 to 400° C., more preferably 50 to 350° C. The heating time during the heat treatment is preferably 1 minute to 6 hours.

[0219] The atmosphere during pressurization is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.

[0220] The ion conductivity (27°C) of the sodium-based solid electrolyte of the present invention is not particularly limited, but is preferably 1.0×10 -6 S / cm or more, more preferably 1.0×10 -4 S / cm or more. The upper limit is not particularly limited, but is often 1.0×10 -2 S / cm or less.

[0221] The dispersion liquid containing the sodium-based solid electrolyte of the present invention can be preferably used as a dispersion liquid for forming a solid electrolyte layer.

[0222] The method for forming a solid electrolyte layer using the above-mentioned solid electrolyte layer forming dispersion is not particularly limited, but a method for forming a solid electrolyte layer by applying the solid electrolyte layer forming dispersion to an object can be cited. In addition, as required, the formed coating film can be subjected to a pressure treatment.

[0223] The coating method of the solid electrolyte layer-forming dispersion is not particularly limited, and examples thereof include spray coating, spin coating, dip coating, slit coating, spray coating, aerosol deposition, thermal spraying, and bar coating.

[0224] In addition, after applying the dispersion for forming a solid electrolyte layer, the obtained coating film may be dried as needed. The drying temperature is not particularly limited, but as a lower limit, it is preferably 30°C or more, more preferably 60°C or more, and further preferably 80°C or more. As an upper limit of the drying temperature, it is preferably 300°C or less, and more preferably 250°C or less.

[0225] The method of pressurizing the coating film is not particularly limited, but a method using a known pressurizing device (for example, a hydraulic cylinder press) can be mentioned.

[0226] The pressure applied during the pressurization treatment is not particularly limited, but is preferably 5 to 1500 MPa, more preferably 300 to 600 MPa, from the viewpoint of obtaining a more excellent ion conductivity of the formed solid electrolyte layer.

[0227] The time of the pressurization treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, from the viewpoint of better ion conductivity of the formed solid electrolyte layer and productivity.

[0228] Furthermore, during the pressurization treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is more preferably 1 minute to 6 hours.

[0229] The atmosphere during pressurization is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.

[0230] (Electrode Forming Composition)

[0231] The sodium-based solid electrolyte of the present invention is also preferably used as a component of an electrode-forming composition. That is, the electrode-forming composition is preferably a composition containing the sodium-based solid electrolyte of the present invention and an active material.

[0232] The mixing ratio of the sodium-based solid electrolyte and the active material in the electrode forming composition is not particularly limited, but the content ratio of the sodium-based solid electrolyte to the active material (mass of the sodium-based solid electrolyte / mass of the active material) is preferably 0.01 to 50, more preferably 0.05 to 20.

[0233] The sodium-based solid electrolyte contained in the electrode-forming composition is as described above.

[0234] Examples of the active material include negative electrode active materials and positive electrode active materials. The active material will be described in detail below.

[0235] (Negative electrode active material)

[0236] The negative electrode active material is not particularly limited as long as it can reversibly store and release sodium ions. Examples of the negative electrode active material include carbonaceous materials and oxides of metal elements or semi-metal elements.

[0237] The carbonaceous material used as the negative electrode active material is a material substantially composed of carbon. As the carbonaceous material, a hardly graphitizable carbonaceous material (hereinafter also referred to as "hard carbon") is preferred.

[0238] The carbonaceous material is obtained by, for example, calcining petroleum pitch, carbon black such as acetylene black (AB), graphite (natural graphite and artificial graphite such as vapor-grown graphite), and various synthetic resins such as PAN (polyacrylonitrile) resin and furfuryl alcohol resin.

[0239] The oxide of the metal element or semi-metal element used as the negative electrode active material is not particularly limited as long as it is an oxide that can absorb and release sodium, and examples thereof include Na2Ti3O7 and Na3Ti2(PO4)3.

[0240] The shape of the negative electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the negative electrode active material is not particularly limited, but preferably 0.1 to 60 μm, more preferably 0.5 to 20 μm, and further preferably 1.0 to 15 μm.

[0241] The volume average particle size is measured by the following procedure.

[0242] Use water (heptane in the case of unstable substances in water) to dilute the negative electrode active material in a 20 mL sample bottle to prepare a 1% dispersion. The diluted dispersion sample was irradiated with 1 kHz ultrasound for 10 minutes and then used in the test immediately. Using the dispersion sample and using a laser diffraction / scattering particle size distribution measuring device, 50 data readings were performed using a measuring quartz cell at a temperature of 25°C to obtain the volume average particle size. For other detailed conditions, refer to JIS Z 8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Make 5 samples for each level and use their average value.

[0243] The negative electrode active material may be used alone or in combination of two or more.

[0244] (Positive electrode active material)

[0245] The positive electrode active material is not particularly limited as long as it can reversibly occlude and / or release sodium ions. As the positive electrode active material, for example, a transition metal oxide containing at least a transition metal element can be cited, preferably a transition metal oxide containing at least one transition metal element selected from Cr, Fe, Mn, Co and Ni.

[0246] Examples of transition metal oxides that function as positive electrode active materials include Na2Fe2(SO4)3, Na7V4(PO4)P2O7, Na4CO3(PO4)2P2O7, Na4MnCr(PO4)3, and NaMO2 (M represents a transition metal element. For example, NaFe 1 / 2Ni 1 / 2 O2, etc.), Na 2 / 3 Mn 1 / 2 Fe 1 / 2 O2, Na2Mn3O7, Na 2 / 3 Mg 0.28 Mn 0.72 O2, Na2RuO3, Na 1.3Nb 0.3 Mn 0.4 O2、Na 0.6 Li 0.2 Mn 0.8 O2, Na2Mn[Fe(CN)6] and β-NaMnO2.

[0247] The shape of the positive electrode active material is not particularly limited, but preferably particulate. The volume average particle size of the positive electrode active material is not particularly limited, but preferably 0.1 to 50 μm. The volume average particle size of the positive electrode active material particles can be measured in the same manner as the volume average particle size of the negative electrode active material described above.

[0248] The positive electrode active material obtained by the calcination method can be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.

[0249] The positive electrode active material may be used alone or in combination of two or more.

[0250] The electrode-forming composition may contain other components in addition to the sodium-based solid electrolyte and the active material.

[0251] The electrode-forming composition may contain a conductive auxiliary agent.

[0252] As the conductive auxiliary agent, a substance generally known as a conductive auxiliary agent can be used. As the conductive auxiliary agent, for example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjen black and furnace black, amorphous carbon such as needle coke, fibrous carbon such as vapor-grown carbon fiber and carbon nanotubes, and carbonaceous materials such as graphene and fullerene can be cited as electron conductive materials. In addition, conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives can be used.

[0253] In addition to the above-mentioned conductive additives, a common conductive additive containing no carbon atom, such as metal powder or metal fiber, may be used.

[0254] In addition, the conductive auxiliary agent refers to an auxiliary agent that does not insert and release Na during battery charging and discharging and does not function as an active material. Therefore, among the conductive auxiliary agents, the substances that function as active materials in the active material layer during battery charging and discharging are also classified as active materials rather than conductive auxiliary agents. Whether or not to function as an active material during battery charging and discharging is not unique, but is determined by the combination with the active material.

[0255] Furthermore, other components include the above-mentioned binder and sodium salt.

[0256] The electrode forming composition may contain a dispersion medium.

[0257] Examples of the dispersion medium include water and various organic solvents.

[0258] As other components in addition to the above-mentioned components, the electrode forming composition may include components selected from the group consisting of ionic liquids, thickeners, cross-linking agents (cross-linking agents that carry out cross-linking reactions by free radical polymerization, condensation polymerization or ring-opening polymerization), polymerization initiators (polymerization initiators that generate acids or free radicals by heat or light, etc.), defoaming agents, leveling agents, dehydrating agents and antioxidants.

[0259] The method of forming an electrode (negative electrode active material layer and positive electrode active material layer) using the above-mentioned electrode forming composition is not particularly limited, but a method of forming an electrode by applying the electrode forming composition can be cited. In addition, the formed coating film can be subjected to pressure treatment as needed.

[0260] The coating method of the electrode-forming composition is not particularly limited, and examples thereof include spray coating, spin coating, dip coating, slit coating, spray coating, aerosol deposition, thermal spraying, and bar coating.

[0261] In addition, after applying the electrode-forming composition, the obtained coating film may be dried as needed. The drying temperature is not particularly limited, but as a lower limit, it is preferably 30°C or more, more preferably 60°C or more, and further preferably 80°C or more. As an upper limit of the drying temperature, it is preferably 300°C or less, and more preferably 250°C or less.

[0262] The method of pressurizing the coating film is not particularly limited, but a method using a known pressurizing device (for example, a hydraulic cylinder press) can be mentioned.

[0263] The pressure applied during the pressurization treatment is not particularly limited, but is preferably 5 to 1500 MPa, more preferably 300 to 600 MPa.

[0264] The time of the pressurization treatment is not particularly limited, but is preferably 1 minute to 6 hours, more preferably 1 to 20 minutes, from the viewpoint of productivity.

[0265] Furthermore, during the pressurization treatment, a heat treatment may be performed. The heating temperature during the heat treatment is not particularly limited, but is preferably 30 to 300° C., and the heating time is preferably 1 minute to 6 hours.

[0266] The atmosphere during pressurization is not particularly limited, and examples thereof include atmospheric air, dry air (dew point -20°C or lower), and an inert gas (for example, argon, helium, and nitrogen) atmosphere.

[0267] <Solid electrolyte sheet>

[0268] The sodium-based solid electrolyte of the present invention may be contained in a solid electrolyte sheet.

[0269] The above-mentioned solid electrolyte sheet is preferably used as a solid electrolyte sheet for a solid-state battery.

[0270] The solid electrolyte sheet can be formed by molding the sodium-based solid electrolyte of the present invention into a sheet. The molding method is not particularly limited, and for example, the sheet can be formed by pressure molding a dispersion containing the sodium-based solid electrolyte of the present invention.

[0271] <Electrode sheets for solid-state secondary batteries>

[0272] The sodium-based solid electrolyte of the present invention may be contained in an electrode sheet for a solid-state secondary battery. In particular, the sodium-based solid electrolyte of the present invention may be contained in an electrode sheet for a solid-state sodium-ion secondary battery.

[0273] Hereinafter, the electrode sheet for solid-state sodium ion secondary batteries will be described in detail.

[0274] The electrode sheet for a solid sodium ion secondary battery of the present invention is a sheet-shaped molded body that can form an electrode active material layer of a solid sodium ion secondary battery, and is preferably used for an electrode or a laminate of an electrode and a solid electrolyte layer.

[0275] Regarding the electrode sheet for solid-state sodium ion secondary battery of the present invention (also referred to as "electrode sheet"), as long as it is an electrode sheet having an active material electrode layer (hereinafter, also referred to as "active material electrode layer") selected from a group including a negative electrode active material layer and a positive electrode active material layer, it can be a sheet having an active material electrode layer formed on a substrate (collector), or a sheet having no substrate and formed by an active material electrode layer. Usually, the electrode sheet is a sheet having a collector and an active material electrode layer, but also includes a method having a collector, an active material electrode layer and a solid electrolyte layer in sequence, and a method having a collector, an active material electrode layer, a solid electrolyte layer and an active material electrode layer in sequence.

[0276] The electrode sheet of the present invention may have other layers in addition to the above-mentioned layers. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the solid-state sodium ion secondary battery described later.

[0277] In the sheet for a solid sodium ion secondary battery of the present invention, at least one layer of the active material electrode layer contains the sodium-based solid electrolyte of the present invention.

[0278] The method for producing the solid sodium ion secondary battery electrode sheet of the present invention is not particularly limited, and it can be produced, for example, by using the electrode-forming composition of the present invention and forming an active material electrode layer.

[0279] For example, there is a method in which the electrode-forming composition is applied on the current collector (optionally with other layers interposed therebetween) to form a coating film, and the coating film is subjected to a pressure treatment.

[0280] Examples of the method for applying the electrode-forming composition and the method for subjecting the coating film to a pressure treatment include the methods described in the section on the electrode-forming composition.

[0281] <Solid-state secondary battery>

[0282] The solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode.

[0283] At least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer preferably contains the sodium-based solid electrolyte of the present invention.

[0284] Furthermore, the present invention also relates to an electrode for a solid secondary battery, which comprises an active material, an active material layer containing the sodium-based solid electrolyte of the present invention, and a current collector.

[0285] Hereinafter, the solid-state sodium ion secondary battery of the present invention will be mainly described in detail.

[0286] The solid-state sodium ion secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode. At least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer comprises a sodium-based solid electrolyte of the present invention.

[0287] The thickness of the negative electrode active material layer, the solid electrolyte layer and the positive electrode active material layer is not particularly limited. Considering the size of a common solid sodium ion secondary battery, the thickness of each layer is preferably 10 to 1000 μm, more preferably 20 μm or more and less than 500 μm.

[0288] The thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is more preferably 50 μm or more and less than 500 μm.

[0289] The positive electrode active material layer and the negative electrode active material layer may each include a current collector on the side opposite to the solid electrolyte layer.

[0290] The solid sodium ion secondary battery of the present invention can be used as a solid sodium ion secondary battery in the state of the above structure according to the application. However, in order to make it into a dry battery form, it is preferably further sealed in an appropriate case for use.

[0291] The shell can be a shell made of metal or a shell made of resin (plastic). As a shell made of metal, for example, a shell made of aluminum alloy and a shell made of stainless steel can be cited. The metal shell is preferably divided into a shell on the positive electrode side and a shell on the negative electrode side, and is electrically connected to the positive electrode collector and the negative electrode collector, respectively. Preferably, the shell on the positive electrode side and the shell on the negative electrode side are joined and integrated via a gasket for preventing short circuits.

[0292] Below, reference Figure 1 , a solid-state sodium ion secondary battery according to an example of a preferred embodiment of the present invention is described, but the present invention is not limited thereto.

[0293] Figure 1 1 is a cross-sectional view schematically showing a solid-state sodium ion secondary battery according to an example of a preferred embodiment of the present invention. Figure 1 The solid-state sodium ion secondary battery 10 shown includes a negative electrode current collector 1 , a negative electrode active material layer 2 , a solid electrolyte layer 3 , a positive electrode active material layer 4 , and a positive electrode current collector 5 in this order.

[0294] At least one of the negative electrode active material layer 2 , the positive electrode active material layer 4 , and the solid electrolyte layer 3 contains the sodium-based solid electrolyte of the present invention.

[0295] Each layer is in contact with each other and is adjacent to each other. By adopting this structure, when charging, electrons (e - ) is supplied to the negative electrode side, so that the sodium ions (Na + ) accumulates here. On the other hand, during discharge, the sodium ions (Na + ) returns to the positive electrode side, so that electrons are supplied to the working portion 6. In the example shown in the figure, a light bulb is used as a model at the working portion 6 and is lit by discharge.

[0296] The negative electrode active material layer 2 contains the above-mentioned negative electrode active material.

[0297] The positive electrode active material layer 4 contains the above-mentioned positive electrode active material.

[0298] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electron conductors.

[0299] As the material forming the positive electrode collector, aluminum, aluminum alloy, stainless steel, nickel and titanium can be cited, preferably aluminum or aluminum alloy. In addition, as the positive electrode collector, a positive electrode collector (forming a thin film) treated with carbon, nickel, titanium or silver on the surface of aluminum or stainless steel can also be cited.

[0300] As the material forming the negative electrode collector, aluminum, copper, copper alloy, stainless steel, nickel and titanium can be enumerated, preferably aluminum, copper, copper alloy or stainless steel. In addition, as the negative electrode collector, a negative electrode collector processed by carbon, nickel, titanium or silver on the surface of aluminum, copper, copper alloy or stainless steel can also be enumerated.

[0301] The current collector is generally in the form of a film or a sheet, but may be in other shapes.

[0302] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm.

[0303] Furthermore, it is also preferable to generate irregularities on the surface of the current collector by surface treatment.

[0304] The method for producing the solid sodium ion secondary battery is not particularly limited, and known methods may be mentioned. Among them, a method using the electrode-forming composition and / or the solid electrolyte layer-forming dispersion is preferred.

[0305] For example, a positive electrode forming composition containing a positive electrode active material can be applied to a metal foil as a positive electrode collector to form a positive electrode active material layer, and then a solid electrolyte layer is formed by applying a dispersion liquid on the positive electrode active material layer to form a solid electrolyte layer. In addition, a negative electrode forming composition containing a negative electrode active material is applied to the solid electrolyte layer to form a negative electrode active material layer, and a negative electrode collector (metal foil) is overlapped on the negative electrode active material layer, and then the obtained laminate is subjected to a pressurization treatment, thereby obtaining a solid-state sodium ion secondary battery having a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer. It can also be sealed in a housing to make a desired solid-state sodium ion secondary battery.

[0306] Furthermore, a solid-state sodium ion secondary battery can be manufactured by reversing the formation method of each layer, forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode collector, and stacking a positive electrode collector.

[0307] Furthermore, as another method, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer may be separately produced, and these may be stacked to produce a solid sodium ion secondary battery.

[0308] The solid-state sodium ion secondary battery is preferably initialized after manufacture or before use. The method of initialization is not particularly limited, and can be performed, for example, by performing initial charge and discharge under increased pressure, and then releasing the pressure until the pressure becomes the pressure normally used for the solid-state sodium ion secondary battery.

[0309] (Application of solid-state secondary batteries)

[0310] The solid-state secondary battery (especially solid-state sodium ion secondary battery) of the present invention can be applied to various purposes. The application mode is not particularly limited. For example, when it is carried on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone handset, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a video movie, a liquid crystal television, a handheld cleaner, a portable CD player, a mini disc player, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio and a backup power supply can be cited. As other consumer products, automobiles, electric vehicles, motors, lighting equipment, toys, game equipment, load regulators, clocks, flashlights, cameras and medical equipment (pacemakers, hearing aids and shoulder massagers, etc.) can be cited. In addition, it can be used for various military purposes and space purposes. And, it can also be combined with solar cells.

[0311] Example

[0312] Below, enumerate embodiment and comparative example, feature of the present invention is further specifically described.As long as the material, usage amount, ratio, processing content and processing step etc. shown in the following examples do not depart from the gist of the present invention, then can be changed appropriately.Therefore, the scope of the present invention should not be interpreted restrictively by the specific example shown below.

[0313] <Example 1>

[0314] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), Na2B4O7 (247) powder was ball-milled under the following conditions: pot: stabilized zirconia (YSZ) (45 mL), crushing balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), NBO powder (powdered Na2B4O7 crystals) amount: 1 g, atmosphere: air, and ball mill processing time: 100 hours, thereby obtaining a sodium compound.

[0315] 0.05 g of Na salt, namely Na(FSO2)2N(NaFSI), was added to the obtained sodium compound, and ball milling was performed for 100 hours. The obtained powder was added to water so that the powder concentration became 42 mass %, and ultrasonic dispersion was performed for 30 minutes.

[0316] Next, the obtained dispersion was transferred to a glass petri dish and dried at 120° C. for 2 hours in the atmosphere to obtain a thin film of a sodium-based solid electrolyte. Next, the obtained thin film was peeled off to obtain a powder of a sodium-based solid electrolyte.

[0317] Regarding the analysis of each element in the obtained sodium-based solid electrolyte, sodium and boron were quantitatively analyzed by ICP-OES, and fluorine and sulfur were quantitatively analyzed by combustion ion chromatography (combustion IC). Regarding N, the analysis mass of sulfur was estimated in consideration of each atomic weight in the Na salt, and regarding O, the analysis mass of elements other than O was added and calculated as a difference from the total amount of powder. The results are shown in the table described later.

[0318] <Example 2>

[0319] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), Na2B4O7 (247) powder was ball-milled under the following conditions: pot: stabilized zirconia (YSZ) (45 mL), crushing balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), NBO powder (powdered Na2B4O7 crystals) amount: 1 g, atmosphere: air, and ball mill processing time: 100 hours, thereby obtaining a sodium compound.

[0320] 1.5 g of the obtained sodium compound was placed in 2.76 g of pure water and stirred and mixed. A solution obtained by dissolving 1.66 g of Na(FSO2)2N(NaFSI) in 0.35 g of pure water was added dropwise to the obtained mixture and mixed. The obtained slurry was applied to Al foil using a thin film coater, and the Al foil with the coating was stored in a dryer at a relative humidity of 3% overnight to dry the coating. The dried film was scraped off with a scraper to obtain a powder of a sodium solid electrolyte.

[0321] <Example 3>

[0322] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), Na2B4O7 (247) powder was ball-milled under the following conditions: pot: stabilized zirconia (YSZ) (45 mL), crushing balls: stabilized zirconia (YSZ) (average particle size: 5 mm, number: 50), rotation speed: 370 rpm (revolutions per minute), NBO powder (powdered Na2B4O7 crystals) amount: 1 g, atmosphere: air, and ball mill processing time: 100 hours, thereby obtaining a sodium compound.

[0323] 1.0 g of the obtained sodium compound and 0.04 g of carboxymethyl cellulose were lightly mixed in a mortar, and the obtained mixture was placed in a solution obtained by dissolving 0.8 g of Na(FSO2)2N(NaFSI) in 3.0 g of pure water, and stirred and mixed. The obtained slurry was coated on Al foil using a thin film coater, and the Al foil with the coating was stored in a dryer with a relative humidity of 3% overnight to dry the coating. The dried film was scraped off with a scraper to obtain a powder of a sodium solid electrolyte.

[0324] The ionic conductivity of the sodium-based solid electrolyte obtained in Example 2 measured by the method described below is 1×10 -4 S / cm. The ionic conductivity measured by the method described below using the sodium-based solid electrolyte obtained in Example 3 is 1×10 -4 S / cm.

[0325] <Comparative Example 1>

[0326] A powdered Na2B4O7·10 hydrate crystal (NBO powder) manufactured by FUJIFILM Wako Pure Chemical Corporation (crystalline powder, not amorphous state) was compacted at 27°C (room temperature) at an effective pressure of 220 MPa to obtain a comparative powder compact. The ion conductivity of the obtained powder compact could not be detected.

[0327] <Reference example>

[0328] Using a ball mill (P-7 manufactured by Fritsch Japan Co., Ltd.), Na2B4O7 (NBO) powder was ball-milled under the following conditions: pot: stabilized zirconia (YSZ) (45 mL), crushing balls: stabilized zirconia (YSZ) (average particle size: 5 mm, quantity: 50), rotation speed: 500 rpm, NBO powder (powdered Na2B4O7 crystals) amount: 2 g, atmosphere: air, ball mill processing time: 100 hours, thereby obtaining a sodium compound.

[0329] <Various Reviews>

[0330] (Ionic conductivity measurement)

[0331] The sodium-based solid electrolyte obtained in each example was pressed at 27°C (room temperature) at an effective pressure of 30 MPa to obtain a powder compact. Al foil was set on the surface and back of the obtained powder compact, and the ion conductivity was estimated from the analysis of the arc diameter of the Cole-Cole diagram (Nyquist diagram) obtained from the AC impedance measurement via two Al electrodes (measurement temperature 27°C, applied voltage 50mV, measurement frequency range 1Hz to 1MHz).

[0332] The ionic conductivity obtained is 10 -6 S / cm or more, "A" is entered in the "Ion Conductivity" column of the table described below. -6 If the value is S / cm, enter "B" in that column.

[0333] (X-ray diffraction measurement)

[0334] X-ray diffraction measurements were performed on the sodium-based solid electrolytes obtained in Examples 1 to 3 and the crystal powders of the comparative example using CuKα radiation. The measurement conditions were 0.01° / step and 3° / minute.

[0335] In the obtained diffraction spectrum, the case where there is no peak derived from Na2B4O7 crystals (i.e., the case where there is no peak derived from sodium tetraborate crystals with a peak top located in the range of diffraction angle 2θ of 5.0° to 70.0° and the peak with an intensity ratio of 10.0 or more obtained by the above-mentioned intensity measurement method) is set as "A", and the case where there is a peak derived from Na2B4O7 crystals (i.e., the case where the peak with the above-mentioned intensity ratio of 10.0 or more appears) is set as "B". The measurement results are shown in Table 2 described later.

[0336] In addition, in the X-ray diffraction patterns of the sodium-based solid electrolytes obtained in Examples 1 to 3, the peaks derived from the sodium tetraborate crystals appearing at diffraction angles 2θ in the range of 5.0° to 70.0° all satisfy the above-mentioned intensity ratio of less than 2.0.

[0337] In the table, the "Element Analysis" column shows the composition of the sodium-based solid electrolyte obtained in each example, and shows the molar content of each element as a relative value with the B content set to "4.0". In addition, the molar content of each element recorded in the table is a value rounded to the second decimal place.

[0338] In addition, in Examples 1 to 3, the results of X-ray diffraction measurement of the sodium compound obtained by ball milling the Na2B4O7 powder showed that the diffraction angle 2θ in the obtained diffraction pattern was within the range of 5.0° to 70.0°, and no peak originated from the Na2B4O7 crystal and the intensity ratio relative to the average intensity was 10.0 or more. In addition, the measurement conditions of the X-ray diffraction measurement were 0.01° / step and 3° / minute.

[0339] [Table 1]

[0340]

[0341] [Table 2]

[0342]

[0343] As shown in the above table, the sodium-based solid electrolyte of the present invention exhibits the desired effects.

[0344] Explanation of symbols

[0345] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-solid-state sodium ion secondary battery.

Claims

1. A sodium-based solid electrolyte comprising amorphous sodium tetraborate, water and a sodium salt.

2. The sodium-based solid electrolyte according to claim 1, wherein The molar ratio of the sodium salt to the sodium tetraborate is 0.001 to 1.5, The molar ratio of the water to the sodium tetraborate is 1-15.

3. The sodium-based solid electrolyte according to claim 1, wherein The sodium salt is a compound represented by formula (1), Formula (1) NaN(R f1 SO2)(R f2 SO2) R f1 and R f2 Each independently represents a fluorine atom or a perfluoroalkyl group.

4. A sodium-based solid electrolyte, wherein: The sodium-based solid electrolyte comprises Na, B and O. The sodium-based solid electrolyte further comprises one or more specific elements selected from the group consisting of elements of Group 4 of the periodic table, elements of Group 15 of the periodic table, elements of Group 16 of the periodic table, elements of Group 17 of the periodic table, Si, C, Sc and Y. When the molar amount of Na, O and the specific element is expressed by setting the molar amount of B in the sodium-based solid electrolyte to 4.0, The molar amount of Na is 1.6 to 3.5, The molar amount of O is 6.2 to 25.0, The molar amount of each of the specific elements is 0.01 to 10.

0.

5. A method for producing a sodium-based solid electrolyte, which is the method for producing a sodium-based solid electrolyte according to any one of claims 1 to 4, comprising: Step 1, mechanically grinding the sodium oxide containing Na and B; Step 2, mixing the product obtained in step 1 with water; and Step 3, removing water from the dispersion obtained in step 2 to obtain a sodium-based solid electrolyte, The method for producing the sodium-based solid electrolyte satisfies any one of the following requirements 1 to 3. Requirement 1: The mechanical polishing treatment of step 1 is carried out in the presence of a specific element source, wherein the specific element source includes two or more elements selected from the group consisting of F, Cl, Br, I, S, P, Si, Se, Te, C, Sb, As, Sc, Y, Zr, Ti, Hf, H and N. Requirement 2: In the step 2, the product, water and the specific element source are mixed, Requirement 3: In the step 3, a product obtained by removing water from the dispersion obtained in the step 2 and the specific element source are mixed to obtain the sodium-based solid electrolyte.

6. The method for producing a sodium-based solid electrolyte according to claim 5, which satisfies the requirement 1, and Prior to the step 1, the method further includes a step 0 of mechanically polishing the sodium oxide containing Na and B in an environment where the specific element source is not present.

7. A modified positive electrode active material, comprising a positive electrode active material and a coating layer disposed on the positive electrode active material, wherein: The coating layer comprises the sodium-based solid electrolyte according to any one of claims 1 to 4.

8. A modified negative electrode active material, comprising a negative electrode active material and a coating layer disposed on the negative electrode active material, wherein: The coating layer comprises the sodium-based solid electrolyte according to any one of claims 1 to 4.

9. A solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer includes the sodium-based solid electrolyte according to any one of claims 1 to 4. 10 . An electrode sheet for a solid-state secondary battery, comprising the sodium-based solid electrolyte according to claim 1 . 11 . A solid electrolyte sheet comprising the sodium-based solid electrolyte according to claim 1 .

12. An electrode for a solid-state secondary battery, comprising: An active material layer comprising an active material and a sodium-based solid electrolyte according to any one of claims 1 to 4; and Current collector.

Citation Information

Patent Citations

  • All-solid-state sodium ion secondary battery

    WO2018225494A1